The influence of inoculum types on the chemical characteristics and b-glucan content of tempe gembus - SAMSUL RIZAL; MARIA ERNA KUSTYAWATI; MURHADI MURHADI; MUHAMAMAD AMIN (Society for Indonesian Biodiversity, 2023)
Abstract. Rizal S, Kustyawati ME, Murhadi, Amin M. 2023. The influence of inoculum types on the chemical characteristics and b-glucan content of tempe gembus. Biodiversitas 24: 793-798. Tempe gembus is a type of tempe which is made by fermenting tofu dregs with Rhizopus oligosporus. Tempe gembus has lower nutritional value than soybean tempe. Adding Saccharomyces cerevisiae to manufacture tempe gembus is expected to increase the added value of tempe gembus. The aim of this study was to determine the effect of various types of inoculums on the chemical properties and b-glucan content of tempe gembus. The study used a completely randomized block design (RBD) with 3 repetitions and 7 types of inoculums: commercial tempe inoculum (RAPRIMA) (T1), S. cerevisiae (T2), R. oligosporus (T3), commercial tempe inoculum (RAPRIMA) + commercial yeast (Fermipan) (T4), commercial tempe inoculum (RAPRIMA) + S. cerevisiae (T5), R. oligosporus + Fermipan (T6), and R. oligosporus + S. cerevisiae (T7). Tempe gembus produced was analyzed for the content of fat, protein, ash, water, carbohydrates, and b-glucan. The data obtained was analyzed statistically using one way ANOVA and the Honest Significant Difference (HSD) test. The results showed that the type of tempe inoculum increased the levels of protein, ash, water and b-glucan but decreased the levels of fat and carbohydrates in tempe gembus. A mixture of R. oligosporus and S. cerevisiae produced the best tempe gembus containing 0.69% ?-glucan, 6.98% protein, 0.48% ash, 83.98% water, 8.12% carbohydrates and 0.47% fat.